Predictors of Malignancy in Thyroid Nodules Classified as Bethesda Category III - Liu, Xiaoli; Wang, Jingjing; Du, Wei; Dai, Liyuan; Fang, Qigen (Frontiers in Endocrinology, 2022)
Objective: To determine predictors of malignancy in surgically treated Bethesda category III nodules. Methods: Patients with surgically treated thyroid nodules classified as Bethesda category III were retrospectively enrolled. The association between clinical/sonographic features and postoperative pathology was evaluated using univariate and multivariate analyses. Results: A total of 188 nodules from 184 patients were included. The overall malignancy rate was 54.3%. In univariate analysis, male sex, aspect ratio >1, microcalcification, unclear boundary, BRAFV600E mutation, and nuclear atypia were significantly associated with malignant disease in Bethesda category III nodules. Multivariate analysis confirmed that male sex, aspect ratio >1, microcalcification, and BRAFV600E mutation were independent predictors of malignant disease. Conclusions: Malignant disease was common in Bethesda category III nodules, and surgical treatment was strongly indicated in the presence of male sex, aspect ratio>1, microcalcification, and BRAFV600E mutation.